(untitled) (Prithvi Journal of Research and Innovation, 2019)
Work life and personal life are almost inseparable. The main objective of the study is to find the factors affecting work-life balance and perception of faculty members towards those factors. Descriptive research has been used for the study. Out of the total population, only two hundred and twenty samples were selected employing multi stage sampling. However, only one hundred seventy four questionnaires were duly used for the study. Reliability and validity has been tested with Cronobah’s Alpha of .710 comprising 23 items. Survey questionnaire as a primary source of data were used. The questionnaire was prepared both in English and Nepali script for the easiness of the respondents. Different statistical technique was used like mean, standard deviation, chi-square test, ANOVA test. The SPSS software was used for coding and output of data. The data output was presented in tabular form. The perceptual difference has been identified on the basis of demographic profile. Individual life at work and with family is not the influencing factors, but the other factors were the important factors affecting work life balance. Perceptual difference on the basis of gender, faculty involvement, designation, age and mode of residence has been noted on work-life balance. Lastly, it is recommended to the administration to develop a separate Human Resource Management Cell to maintain work life balance. Future researchers need to conduct research covering faculty members of different colleges. Factor analysis along with Structural Equation Modeling statistical tools need to be used in future studies too.